2021
DOI: 10.1080/09638237.2021.1875424
|View full text |Cite
|
Sign up to set email alerts
|

Keeping well in a COVID-19 crisis: a qualitative study formulating the perspectives of mental health service users and carers

Abstract: Background: People with existing mental health conditions may be particularly vulnerable to the psychological effect of the COVID-19 pandemic. But their positive and negative appraisals, and coping behaviour could prevent or ameliorate future problems. Objective: To explore the emotional experiences, thought processes and coping behaviours of people with existing mental health problems and carers living through the pandemic. Methods: UK participants who identified as a mental health service user (N18), a carer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 25 publications
4
27
0
Order By: Relevance
“…This study is one of the first to measure employees' needs for and supplies of social connections during COVID-19 and to call attention to a significant lack of social interaction and social support in the workplace. This result is in concordance with other studies that have found, more generally, high levels of social isolation and loneliness [3,42], as well as changes in social life and social connections [4,43,44], during the pandemic. Furthermore, our response surface analysis (RSA) challenges the assumption of a fit effect, which is common in previous studies [22].…”
Section: Discussionsupporting
confidence: 93%
“…This study is one of the first to measure employees' needs for and supplies of social connections during COVID-19 and to call attention to a significant lack of social interaction and social support in the workplace. This result is in concordance with other studies that have found, more generally, high levels of social isolation and loneliness [3,42], as well as changes in social life and social connections [4,43,44], during the pandemic. Furthermore, our response surface analysis (RSA) challenges the assumption of a fit effect, which is common in previous studies [22].…”
Section: Discussionsupporting
confidence: 93%
“…Finally, as found in other studies (e.g. Dejonckheere et al, 2021 ; Simblett et al, 2021 ), many participants were remarkably resilient and resourceful, drawing on their experience of managing pre-existing difficulties, despite the new threats posed by the pandemic. As service users have noted elsewhere (Gillard et al, 2021 ), there may be limits on the sustainability of some self-management strategies without access to formal support.…”
Section: Discussionsupporting
confidence: 68%
“…Similarly, detailed time series case analyses of daily emotional trajectories for four women with depression and anxiety-related mental health problems demonstrated variation in coping, resilience and emotional response as lockdown restrictions were introduced in Belgium (Dejonckheere et al, 2021 ). There has been limited in-depth exploration of the particular situations and experiences that may produce these differences, though three qualitative studies with people living with or recovering from mental health problems during the pandemic are particularly helpful—two in the UK (Gillard et al, 2021 ; Simblett et al, 2021 ) and one in Australia (Honey et al, 2021 ). Despite some accounts of coping and resilience, many participants across all three studies had clearly struggled with the pandemic restrictions, describing responses of sadness, fear and anger, negative self-appraisals, worsening mental health and a detrimental impact on wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…The unprecedented challenges and uncertainties associated with have reportedly led to substantial mental health deteriorations, both among healthy individuals and those with pre-existing mental health problems (Banks & Xu, 2020;Cullen et al, 2020;McElory et al, 2020;Simblett et al, 2021;Vindegaard & Benros, 2020;Willis & Chalder, 2021). COVID-19 restrictions have resulted in prolonged waiting lists, concerns surrounding how to provide safe and adequate care remotely and MHWs struggling to maintain their own mental wellbeing (Rosenberg et al, 2020).…”
Section: The Mental Health Implications Of Covid-19mentioning
confidence: 99%